An analysis of the legal and institutional framework in administrative law regulating air pollution in Iraq - Mahdi, Asmaa Abdulkadhim (2018)
Iraq suffers from high degree of air pollution due to industrial development taking place in the country. Air pollution represents a major challenge both today and in the future. The problem is constantly increasing due to growing human needs for transportation, energy, industry, etc. To address the air pollution issues in Iraq, the government has passed some important environmental legislations. These legislations consist of mechanisms allowing the administration to control and maintain air quality. Unfortunately, several obstacles have been identified that affect negatively on these mechanisms making them unable to maintain the air quality. The objectives of the study are to examine administrative and legal mechanisms to control air pollution issues in Iraq, to examine the weakness of these mechanisms in protecting the environment against air pollution and to compare the administrative and legal mechanisms of Iraq with that of the United Kingdom and Malaysia so as to draw relevant lessons. This study is a qualitative research using a case study approach. Indepth interview method was used to generate data from stakeholders including public officials of the Ministry of Environment, legal experts, academics, lawyers, doctors and selected victims of air pollution. Observations were also carried out at the selected locations of air pollution. It also undertook doctrinal legal research to support the findings. Content analysis was done on official reports and statutes as primary sources supported with secondary sources in the form of textbooks, government publications, academic journals, newspaper articles and internet sources. This study found that the laws and policies have not been properly enforced due to various problems including insufficiency, non-implementation, non–coordination, lack of environmental expertise, weak execution and lack of environmental awareness. This study suggests a review of the provisions of the environmental laws in Iraq regarding air protection and where applicable draw lessons from the comparative analysis to offer solutions to these issues. These recommendations should be taken seriously by the Iraqi legislature and stakeholders in addressing the administrative legal and policy mechanisms associated with air pollution in Iraq.